Solid‐State Molecular Nanomagnet Inclusion into a Magnetic Metal–Organic Framework: Interplay of the Magnetic Properties. Issue 2 (11th December 2015) - Mon, Marta; Pascual‐Álvarez, Alejandro; Grancha, Thais; Cano, Joan; Ferrando‐Soria, Jesús; Lloret, Francesc; Gascon, Jorge; Pasán, Jorge; Armentano, Donatella; Pardo, Emilio
Abstract: Invited for the cover of this issue is the group of Emilio Pardo at the University of València and his collaborators. The image depicts the solid‐state incorporation of a metalloporphyrin within the pores of a magnetic metal–organic framework. Read the full text of the article at10.1002/chem.201504176 . Abstract : " Many single‐ion magnets, which are the smallest possible magnetic devices, need the application of an external magnetic field in order to avoid the presence of undesired quantum tunneling effects. " Read more about the story behind the cover in the Cover Profile and about the research itself on page 539 ff. (DOI:10.1002/chem.201504176 ).